2023
DOI: 10.3390/s23031498
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Cavity Sensor for Measurements of Air Humidity under Reduced Pressure

Abstract: A high-sensitivity sensor for measuring moisture content in the air or air humidity under low pressure was designed on the basis of a half-wave coaxial microwave cavity. The method of measuring small variations in the signal phase at a cavity excitation frequency of 1.63 GHz was applied to detect low densities of water vapor. It allows the detection of variations in dielectric air permittivity in the seventh decimal place. A prototype of the sensor was tested in a vacuum chamber. It was calibrated by comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies in this area have shown that reactive properties and negative differential resistance are inextricably linked, and the versatility and simplicity of radio electronic devices based on transistor structures with negative resistance is the prospect of their practical use. Self-oscillating parametric humidity sensors that implement the "humidityfrequency" conversion principle are characterized by simplicity and versatility, as well as accuracy and noise immunity [6,7,22].…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…Studies in this area have shown that reactive properties and negative differential resistance are inextricably linked, and the versatility and simplicity of radio electronic devices based on transistor structures with negative resistance is the prospect of their practical use. Self-oscillating parametric humidity sensors that implement the "humidityfrequency" conversion principle are characterized by simplicity and versatility, as well as accuracy and noise immunity [6,7,22].…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%